Effects of HPMC (Hydroxypropyl methylcellulose) on oil uptake and texture of gluten-free soy donut. Issue 1 (June 2015) - Kim, Jihyun; Choi, Induck; Shin, Woo-Kyoung; Kim, Yookyung
Abstract: We developed a gluten-free soy donut with HPMC (Hydroxypropyl methylcellulose) and investigated the effects of HPMC on the quality of a soy donut depending on the different ways of its addition. Soy donuts were prepared under three conditions: only soy (S), HPMC added soy (SH), and HPMC added and coated soy (SHC). A wheat donut was used as a control. The results showed that the S donut had approximately two times lower oil uptake and moisture loss compared to wheat control; however, the S donut had 30% less specific volume and three times harder texture. HPMC addition in soy donut (30.7 N) resulted in a decrease in the hardness to 23.5 N for SH and 20.8 N for SHC. In addition, the incorporation of HPMC gave soy donuts the further decrease in the oil uptake and moisture loss. For the method of adding HPMC, the SHC donut had less oil uptake and a softer texture than the SH. Among soy donuts, SHC has the desirable intensities of sensory attributes (texture and mouthfeel), resulting in the highest overall preference score, closer to that of the wheat donut. The addition of HPMC improves the quality of gluten-free donuts made entirely with soy flour. Highlights: We developed a 100% soy donut with HPMC. Soy donut had lower oil uptake, however, it has less volume and harder texture. Addition of HPMC to soy donut improved volume and hardness as well as oil uptake. Addition of and coating with HPMC have significant effects on the quality of donut. Soy could be a good ingredient for gluten-free food with a healthy and new flavor.